Efficacy of ACL injury risk screening methods in identifying high‐risk landing patterns during a sport‐specific task. (12th June 2016) - Fox, A. S.; Bonacci, J.; McLean, S. G.; Saunders, N.
Abstract : Screening methods sensitive to movement strategies that increase anterior cruciate ligament (ACL) loads are likely to be effective in identifying athletes at‐risk of ACL injury. Current ACL injury risk screening methods are yet to be evaluated for their ability to identify athletes' who exhibit high‐risk lower limb mechanics during sport‐specific maneuvers associated with ACL injury occurrences. The purpose of this study was to examine the efficacy of two ACL injury risk screening methods in identifying high‐risk lower limb mechanics during a sport‐specific landing task. Thirty‐two female athletes were screened using the Landing Error Scoring System (LESS) and Tuck Jump Assessment. Participants' also completed a sport‐specific landing task, during which three‐dimensional kinematic and kinetic data were collected. One‐dimensional statistical parametric mapping was used to examine the relationships between screening method scores, and the three‐dimensional hip and knee joint rotation and moment data from the sport‐specific landing. Higher LESS scores were associated with reduced knee flexion from 30 to 57 ms after initial contact ( P = 0.003) during the sport‐specific landing; however, no additional relationships were found. These findings suggest the LESS and Tuck Jump Assessment may have minimal applicability in identifying athletes' who exhibit high‐risk landing postures in the sport‐specific task examined.